P57 in Hydatidiform Moles: Evaluation of Antibodies and Expression in Various Cell Types. Issue 9 (October 2020) - Lund, Helle; Nielsen, Søren; Grove, Anni; Vyberg, Mogens; Sunde, Lone
Abstract : The protein p57 is encoded by CDKN1C. This gene is known to be paternally imprinted and maternally expressed in cytotrophoblasts and villous stromal cells. We present a method for evaluating p57 antibodies (Abs) in hydatidiform mole (HM) and demonstrate the results for 4 p57 Abs in various cell types. Five cases of complete HM, diploid with 2 paternal genome sets (CHM;PP), 5 cases of partial HM, triploid with 2 paternal and 1 maternal genome sets (PHM;PPM), and 5 cases of non-HM, with diploid biparental genomes (non-HM;PM) were stained with p57 Abs: 57P06, EP183, KP10, and KP39. Assessment of the fraction of nuclei stained, and the intensity of staining of the nuclei and cytoplasm was performed. For evaluation of the Abs, the observations in cytotrophoblasts, villous stromal cells, maternal decidual cells, and intermediate trophoblasts were scored. The fraction of stained nuclei in cytotrophoblasts and villous stromal cells and the staining of cytoplasm showed to be important parameters in the evaluation of the Abs. 57P06 was evaluated as optimal. KP10 showed moderate cytoplasmatic staining in maternal decidual cells and intermediate trophoblasts, and was evaluated as good. EP183 was evaluated as poor, primarily due to nuclear staining in ≥10% of the villous stromal cells in CHM;PP. KP39 was evaluated as poor, primarily due to strong cytoplasmatic staining in some cytotrophoblasts and villous stromal cells. A structured testing of p57 for diagnosing HM is recommended. No nuclear staining was observed in syncytiotrophoblasts of CHM;PP, indicating that in syncytiotrophoblasts also, CDKN1C is paternally imprinted. Abstract : Supplemental Digital Content is available in the text.